2009
DOI: 10.1080/03634520802527288
|View full text |Cite
|
Sign up to set email alerts
|

Communication Across the Curriculum and in the Disciplines: A Call for Scholarly Cross-curricular Advocacy

Abstract: Communication-across-the-curriculum (CXC) programs provide assistance to other disciplines on the teaching and learning of communication*meeting an increasingly important need for students not only to be content specialists, but also coherent communicators. Research emerging from this initiative details programmatic challenges and emphases, but also provides insight into the unique interdisciplinary issues involved with teaching communication in other disciplinary cultures. Through a systematic thematic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…She also noted an obvious need for more specialized integration of communication in other disciplinary classrooms (i.e., CID). In addition, CXC is often criticized for its lack of theoretical sophistication and rigor (Dannels, 2001;Dannels & Gaffney, 2009;Darling, 2005). In response, Dannels (2001) created the CID model that has a discipline-specific agenda.…”
Section: (Engaged) Communication In the Disciplinesmentioning
confidence: 98%
See 1 more Smart Citation
“…She also noted an obvious need for more specialized integration of communication in other disciplinary classrooms (i.e., CID). In addition, CXC is often criticized for its lack of theoretical sophistication and rigor (Dannels, 2001;Dannels & Gaffney, 2009;Darling, 2005). In response, Dannels (2001) created the CID model that has a discipline-specific agenda.…”
Section: (Engaged) Communication In the Disciplinesmentioning
confidence: 98%
“…The earliest efforts to focus on communication in different disciplines were described in the communication-across-the-curriculum (CXC) framework, which is used to provide noncommunication majors with foundational communication instruction (Dannels & Gaffney, 2009). The framework is derived from the idea that students need to not only specialize in their content area, but also be effective and efficient communicators (Darling, 2005).…”
Section: (Engaged) Communication In the Disciplinesmentioning
confidence: 99%
“…This cost-cutting device, combined with the increased inclusion of the basic course in general education may suggest a need to explore instructional delivery options such as a communication across the curriculum program. Some researchers make a case for this instructional method and consider it a form of scholarly crosscurricular advocacy (Dannels & Gaffney, 2009). When contemplating such a program, these sorts of questions arise.…”
Section: Discussion Of Results Of the Present Studymentioning
confidence: 99%
“…Dannels and Housley Gaffney (2009) observed that even when oral communication assignments in academics were intended to prepare students for the workplace, academic standards and expectations were reinforced (See, e.g., Dannels, 2003;Dannels, Anson, Bullard, & Peretti, 2003;Dannels & Norris Martin, 2008;Smith, 2005). CXC research during the third era is grounded in the CID theoretical framework, making it pertinent to the current study of dietetics.…”
mentioning
confidence: 99%
“…Additionally, from this study issues of relevance to CXC may emerge, signaling directions for future exploration and also suggest areas for the cultivation of interdisciplinary partnerships with other discipline practitioners and perhaps external entities (Dannels & Housley Gaffney, 2009). …”
mentioning
confidence: 99%